2011 IEEE Vehicular Technology Conference (VTC Fall) 2011
DOI: 10.1109/vetecf.2011.6093250
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Antenna Selection for Wireless LANs with Directional & Omni-Directional Elements

Abstract: Abstract-Throughput and packet error rate are analysed in a home environment for two different 3x3 wireless LAN solutions. A 3x3 EBF approach (using three radio chains) is compared with a reduced cost 2x2 architecture (using two radio chains). In the 2x2 solution the optimum antenna pair is selected from the same set of three antennas at the AP and client. The impact of directional, as well as omni-directional, antenna elements is considered. The spatial and temporal characteristics of the inhome channels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…eigen-beamforming or spatial-multiplexing) will be taken into account. This is part of our future work and some initial results can be found in [5] [6].…”
Section: Antenna Radiation Patternsmentioning
confidence: 95%
See 1 more Smart Citation
“…eigen-beamforming or spatial-multiplexing) will be taken into account. This is part of our future work and some initial results can be found in [5] [6].…”
Section: Antenna Radiation Patternsmentioning
confidence: 95%
“…The antennas used at the access point (AP) and client influence the perceived channel quality and must be carefully considered. Previous measurements [4] and simulations [5] [6] have shown that different antenna configurations and orientations have a significant impact on performance.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was fully described in [15] and subsequently used in a number of our Wireless LAN and cellular network studies, for instance [21] and [22]. Without sacrificing accuracy, abstraction is many hundreds of times faster than full bit-level simulation.…”
Section: Abstraction Simulatormentioning
confidence: 99%
“…To perform system level analysis in a computationally efficient and scalable manner, a physical layer abstraction technique RBIR was used to predict the packet error rate (PER) for a given channel realisation across the allocated OFDM subcarriers. This technique was fully described in [13] and subsequently used in a number of our Wireless LAN and cellular network studies [17,18]. Without sacrificing accuracy, abstraction is many hundreds of times faster than full bit-level simulation.…”
Section: Network Simulator and Parametersmentioning
confidence: 99%